THE INFLUENCE OF DIGITAL MARKETING ON DECISIONS TO PURCHASE MOISTURIZER PRODUCTS USING ELECTRONIC WORD OF MOUTH AS MEDIATION - Wulandari, Ayu Dwi; Kurniati, Rini Rahayu; Chanafi, Ainul (Universitas Islam Malang, 2023)
Thisi researchi aimsi to analyzei the influencei of digitalo marketingi on purchasing decisions for moisturizer products using electronic word of mouth as mediation for The Originote moisturizer products on Tiktok social media. The methodi usedi in this researchi is a descriptivei quantitativei method. The data analysis techniquei uses Patrial Least Square (PLS) and hypothesis testing using bootstrapping.The researchi results showi that the Digital Marketingi variable has a positive and significanti influence on purchasing decisionsi for The Originote moisturizer on Tiktok social media. The Digitali Marketingi variablei has a positive and significant effect on E-WOM. The E-WOM variablei has a positivei and significanti influence on the decision to purchase The Originote moisturizer on Tiktok social media. The Digital Marketing variable mediated by E-WOM has a positive and significant influence on the decision to purchase The Originote moisturizer on Tiktok social media.